The role of school principals in the development of human relations in the post basic schools in the Sultanate of Oman - Salim Juma Alarimy, Aisha; Salim Juma, Mahfooda; Ibrahim, Mohd Burhan (Institute of Interdisciplinary Business Research, 2012)
The purpose of this study was to identify the role principals in the development of human relations in high schools. The study sample of the study comprised of teachers and administrators from different schools selected randomly according to their gender, qualification, experience, and region. A School Human Relations (SHR) questionnaire was distributed to a sample of 780 of administrators and teachers in six education regions. Data collected was analysed using descriptive and inferential statistics (MANOVA) were used to analyse that data. The results of the study revealed that there were statistically significant differences among teachers and administrators on the principals’ role in human relation according to their qualification and experience. Based on the findings of this research it was that recommended that there was need to strengthen and promote skill development of human relationships in teachers and administrators through training them and to emphasize the importance of professional development and a culture of self-development for school administrators and teachers.